Human uterine transplantation: a review of outcomes from the first 45 cases. (13th August 2019) - Jones, BP; Saso, S; Bracewell‐Milnes, T; Thum, M‐Y; Nicopoullos, J; Diaz‐Garcia, C; Friend, P; Ghaem‐Maghami, S; Testa, G; Johannesson, L; Quiroga, I; Yazbek, J; et al.
Abstract : Uterine transplantation restores reproductive anatomy in women with absolute uterine factor infertility and allows the opportunity to conceive, experience gestation, and acquire motherhood. The number of cases being performed is increasing exponentially, with detailed outcomes from 45 cases, including nine live births, now available. In light of the data presented herein, including detailed surgical, immunosuppressive and obstetric outcomes, the feasibility of uterine transplantation is now difficult to refute. However, it is associated with significant risk with more than one‐quarter of grafts removed because of complications, and one in ten donors suffering complications requiring surgical repair. Tweetable abstract: Uterine transplantation is feasible in women with uterine factor infertility, but is associated with significant risk of complication. Tweetable abstract: Uterine transplantation is feasible in women with uterine factor infertility, but is associated with significant risk of complication.